Sulfoxide Reductases and Applications in Biocatalytic Preparation of Chiral Sulfoxides: A Mini-Review - Peng, Tao; Cheng, Xiaoling; Chen, Yongzheng; Yang, Jiawei (Frontiers in Chemistry, 2021)
Chiral sulfoxides are valuable organosulfur compounds that have been widely used in medicinal and organic synthesis. Biocatalytic approaches for preparing chiral sulfoxides were developed in the past few years, mainly through asymmetric oxidation of prochiral sulfides. Recently, the application of sulfoxide reductase to prepare chiral sulfoxides through kinetic resolution has emerged as a new method, exhibiting extraordinary catalytic properties. This article reviews the chemical and biological functions of these sulfoxide reductases and highlights their applications in chiral sulfoxide preparation.